Defective epithelial barrier in chronic rhinosinusitis: The regulation of tight junctions by IFN-γ and IL-4 - Soyka, Michael B.; Wawrzyniak, Paulina; Eiwegger, Thomas; Holzmann, David; Treis, Angela; Wanke, Kerstin; Kast, Jeannette I.; Akdis, Cezmi A. (Journal of allergy and clinical immunology, 2012)
Chronic rhinosinusitis (CRS) is a common disease with still unclear pathophysiologic mechanisms. Epithelial tight junctions (TJs) have been shown to be involved in different chronic disorders, including bronchial asthma, inflammatory bowel diseases, and skin disorders. The regulation of epithelial barrier function and TJ expression has not been extensively studied in patients with CRS and in the paranasal sinus epithelium thus far. We sought to elucidate the TJ expression pattern in the epithelium of the sinonasal mucosa and its regulation in patients with CRS. Trans-tissue resistance was measured in biopsy specimens from healthy control subjects and patients with CRS with and without nasal polyps. TJ protein expression was determined by using immunofluorescence, Western blotting, and real-time PCR. Primary epithelial cell cultures from patients with CRS and control subjects were used in air-liquid interface (ALI) cultures for the measurement of transepithelial resistance (TER) and TJ expression. The effect of IFN-γ, IL-4, and IL-17 on ALI cultures was assessed. A decreased trans-tissue resistance was found in biopsy specimens from patients with CRS with nasal polyps along with an irregular, patchy, and decreased expression of the TJ molecules occludin and zonula occludens 1. TER was reduced in ALI cultures from patients with CRS with nasal polyps. The cytokines IFN-γ and IL-4 decreased TER, whereas IL-17 did not have any influence on epithelial integrity. A defective epithelial barrier was found in patients with CRS with nasal polyps along with a decreased expression of TJ proteins. The disruption of epithelial integrity by IFN-γ and IL-4 in vitro indicates a possible role for these proinflammatory cytokines in the pathogenesis of patients with CRS.